Overcoming the Stromal Barrier of the Cornea with a Peptide Conjugate Nano‐Assembly to Combat Fungal Keratitis. Issue 10 (15th January 2023) - Ju, Xiaoyan; Wu, Liping; Gao, Ning; Tian, Ye; Lu, Guojun; Gao, Yichen; Zhao, Shaozhen; Niu, Zhongwei; Yang, Ruibo
Abstract: Fungal hyphae deeply invade the cornea in fungal keratitis. The corneal stroma hinders the infiltration of antifungal drugs and reduces their bioavailability. Here, this work reports a peptide conjugate nano‐assembly that permeates the stroma and kills the pathogen without irritating the ocular cornea. The hydrophilic surface of the nano‐assembly ensures deep permeation into the stroma. When encountering a fungal hyphal cell, the nano‐assembly disassembles and exposes the α ‐helical peptide to destroy the fungal membrane, thus inactivating the pathogen. In a rabbit model of fungal keratitis, the nano‐assembly exhibits a better therapeutic effect than commercially available natamycin ophthalmic suspension. Peptide conjugates with a nano‐assembled structure and assembly–disassembly behavior could serve as the foundation of a new therapy for fungal keratitis. Abstract : A peptide conjugate nano‐assembly (PCNA) permeates deeply into the corneal stroma due to its hydrophilic outer surface. When it encounters a negatively charged fungal membrane, the PCNA disassembles on the cell surface, exposing the α ‐helix structure that kills the fungal cell. This unique strategy is more effective than commercially available natamycin ophthalmic suspension for treating fungal keratitis.